2017
DOI: 10.5897/ajbr2017.0955
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, antibiotic promotion and in vivo toxicity of Piper nigrum and Syzygium aromaticum essential oil

Abstract: The antimicrobial activity of spices of human daily diet has been widely demonstrated. Yet, their capacity of promoting antibiotic activity has not been explored adequately. In this work, the chemical composition of essential oils of Piper nigrum and Syzygium aromaticum from Chad were determined and their antimicrobial effect in combination with different antibiotics towards Staphylococcus aureus, Salmonella enteritidis and Salmonella typhi were assessed. Moreover, the in vivo toxicity of the essential oils al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…For this purpose, the biological activity of other major and minor components of lavender essential oils should be tested in analogous conditions to identify the remaining active compounds. Some authors have shown synergistic effects with gentamicin for other essential oils against Gram-positive and Gram-negative bacteria [1,44,[49][50][51]. This was confirmed in our previous study on commercial lavender essential oil [7] and the currently studied oils isolated from different cultivars and morphological parts of lavender, whose combinations with gentamicin have not yet been examined.…”
Section: Discussionsupporting
confidence: 73%
“…For this purpose, the biological activity of other major and minor components of lavender essential oils should be tested in analogous conditions to identify the remaining active compounds. Some authors have shown synergistic effects with gentamicin for other essential oils against Gram-positive and Gram-negative bacteria [1,44,[49][50][51]. This was confirmed in our previous study on commercial lavender essential oil [7] and the currently studied oils isolated from different cultivars and morphological parts of lavender, whose combinations with gentamicin have not yet been examined.…”
Section: Discussionsupporting
confidence: 73%